Chronic thromboembolic pulmonary hypertension is a clot you cannot swat - G. Jay Bishop, MD, FACP, FSVM, RPVI (Journal of Vascular Surgery Cases and Innovative Techniques, 2019)
A 49-year-old man with progressive dyspnea on exertion and a remote history of syncope presented with hypotension and acute right ventricular failure, and was ultimately diagnosed with acute pulmonary embolism. Laboratory data revealed a prolonged activated partial thromboplastin time, which confounded treatment options. He was ultimately diagnosed with anti-phospholipid syndrome and factor XII deficiency, and underwent a thromboendarterectomy procedure with resolution of right ventricular failure and symptoms. Careful attention to history, initial physical examination manifestations, and clinical data often permit a timely diagnosis of and treatment for chronic thromboembolic pulmonary hypertension. Keywords: Thrombus, Pulmonary embolism, Pulmonary hypertension, CTEPH